Preparation and application of sweat ascorbic acid detection sensor based on screen-printed electrode and wood substrate
By using screen printing technology to prepare three-electrode sensors on flexible wood substrates, the problems of high electrode preparation cost and low hydrophilicity of substrate materials in the prior art are solved, and low cost, high hydrophilicity and directional conduction are achieved. Sweat sensor improves the performance and application range of ascorbic acid detection.
Patent Information
- Application Number
- CN202411275900.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-12
AI Technical Summary
The electrode preparation of existing sweat ascorbic acid detection sensors is not easy to prepare and costly. The base material is low in hydrophilicity and cannot deliver sweat in a directional manner, which affects the performance and application range of the sensor.
A three-electrode sensor is prepared on a flexible wood substrate by using screen printing technology. The wood substrate after removing lignin provides a sensor with high hydrophilicity and directed sweat conduction, reducing production costs and improving detection efficiency.
It realizes a low-cost and simple production of high-hydrophilic sensor, improves the sensitivity and response speed of ascorbic acid detection, and enhances the stability and application range of the sensor.
Smart Images

Figure CN119322104A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of wearable sensors, and in particular relates to the preparation and application of a sweat ascorbic acid detection sensor which is simple in structure and low in cost and adopts screen printing and a wood substrate. Background Art
[0002] Sweat-based ascorbic acid detection equipment has gradually gained attention due to its real-time nature, convenience and other advantages. Sweat, as a body fluid rich in biomarkers, is easy to collect and preserve, making it an ideal medium for measuring ascorbic acid levels. Among sweat ascorbic acid detection sensors, sensors based on electrochemical technology have been the most prominent due to their advantages such as high sensitivity, rapid response, and miniaturization. Sensors usually include two parts: a detection electrode and a substrate. (1) For detection electrodes, there are enzyme catalysis and non-enzyme catalysis methods. Although enzyme electrodes are favored for their excellent selectivity, the inactivity of enzymes may affect the stability of detection, and the development and production costs of such electrodes are high, and the manufacturing process is complicated. Although non-enzyme catalytic electrodes use catalysts such as graphene and precious metals to enhance the reaction, the preparation process of graphene is complicated and costly, and the deposition process of metal catalysts is cumbersome and expensive, which increases the overall production cost and is not conducive to large-scale promotion and use. (2) In terms of substrates, although common materials such as polyethylene terephthalate (PET) and polydimethylsiloxane (PDMS) are easily available and have a certain degree of flexibility, their low hydrophilicity may affect the uniform distribution of sweat on the sensor surface, thereby negatively affecting performance. In addition, the hydrophobic properties of these substrates may destroy the natural wetting environment of the skin surface, reducing comfort and biocompatibility during long-term wear. Another problem is that these substrate materials cannot achieve directional transport of analytes in sweat and can only rely on diffusion, which slows down the process of sweat and the ascorbic acid molecules it contains reaching the detection electrode, which may lead to a decrease in analyte concentration, thereby affecting the response speed and detection sensitivity of the sensor. In summary, although the above sweat ascorbic acid electrochemical detection technology has shown a certain degree of reliability in measuring the concentration of ascorbic acid in sweat, the main challenges faced by current technologies are the inconvenient electrode preparation, high cost, low hydrophilicity of the substrate material, and the inability to transport sweat in a directional manner. These problems will limit the overall performance and application range of the sensor. Therefore, it is necessary to prepare an electrochemical sensor that is easy to prepare, low in cost, has high hydrophilicity and can directional conduct sweat to optimize the detection process of ascorbic acid. Summary of the invention
[0003] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a simple and low-cost preparation method of a sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate.
[0004] Another object of the present invention is to provide a sensor for sweat ascorbic acid detection prepared by the above method, which is simple to prepare, low-cost and highly hydrophilic. The sensor includes three electrodes and a flexible wood substrate. Carbon slurry and Ag / AgCl drop are screen printed on the flexible wood substrate to form three electrodes. The flexible wood substrate is treated to remove some lignin and is used to collect, store and transport sweat to the electrodes.
[0005] Another object of the present invention is to provide the application of the above-mentioned simple, low-cost and highly hydrophilic sensor in the detection of ascorbic acid in sweat. During the detection process, ascorbic acid is oxidized on the electrode, and the concentration of ascorbic acid is analyzed by measuring the current of the oxidation reaction.
[0006] The purpose of the present invention is achieved through the following solutions:
[0007] A method for preparing a sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate comprises the following steps:
[0008] Step (1): Preparation of flexible wood substrate
[0009] The wood chips are immersed in a mixed aqueous solution containing NaOH and Na2SO3, and then vacuum impregnated. After the impregnation, the wood chips are immersed in boiling water to remove the chemicals, and then dried to obtain a flexible wood substrate with part of the lignin removed.
[0010] Step (2): Silkscreen wax printing
[0011] The flexible wood substrate is fixed on a screen printing table, and solid wax is scraped onto the flexible wood substrate through the screen, and then the flexible wood substrate is heated to melt the solid wax particles passing through the mesh, and the solid wax particles are turned into liquid and absorbed by the substrate to form a hydrophobic barrier. The hydrophilic area is not scraped with the solid wax, and the hydrophobic and hydrophilic areas are separated. The flexible wood substrate is then cooled to room temperature to obtain a wax-printed patterned flexible wood substrate;
[0012] Step (3): Three-electrode printing
[0013] Three electrodes, namely, a working electrode, a counter electrode and a reference electrode, are printed on the hydrophilic area of a wax-patterned flexible wood substrate, and then dried to obtain a sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate.
[0014] As a simple, efficient and relatively mature preparation process, screen printing technology has shown significant cost-effectiveness in the field of sensor preparation. This method is applicable to a variety of substrate materials, including wood, plastic and metal, and provides a low-cost solution for quickly customizing electrode patterns on a variety of substrates. Through the template, screen printing can accurately transfer different types of inks to the surface of the material, realizing the rapid and precise production of electrode patterns. In addition, this technology can distinguish the hydrophilic and hydrophobic areas of the substrate through simple screen wax printing, providing more flexibility and functionality for sensor design. In terms of preparation cost, the advantage of screen printing technology is the economy of its raw materials and preparation tools. Whether it is ink or printing equipment, low-cost commercial materials and devices can be selected, which greatly reduces the production cost of sensors. The application of screen printing technology in sensor preparation provides the possibility for simple and low-cost production of sensors. On the other hand, the use of flexible wood as the substrate material of the sensor is conducive to the collection and transmission of sweat. After removing part of the lignin from the wood substrate, it not only has the flexibility and water absorption similar to paper, but also has higher mechanical strength than paper. In addition, the natural pores and porous structure of wood are extremely suitable for transporting and storing sweat. These tiny channels simulate the water transport system of plants and can directly and quickly transport sweat to the electrodes. This transport mechanism does not rely on diffusion, reduces time delays and sample loss, thereby improving the accuracy and stability of the sensor, making it an ideal sensor substrate material. In summary, by combining screen printing technology and flexible wood substrates, a sensor with simple preparation, low cost, high hydrophilicity and directional conduction of sweat can be manufactured.
[0015] The wood chips described in step (1) are preferably balsa wood chips.
[0016] The concentrations of NaOH and Na2SO3 in the mixed aqueous solution containing NaOH and Na2SO3 described in step (1) are ≥1 mol / L and ≥0.4 mol / L, respectively.
[0017] The amount of the mixed aqueous solution containing NaOH and Na2SO3 in step (1) is sufficient to allow the wood chips to be completely immersed in the mixed aqueous solution containing NaOH and Na2SO3.
[0018] The vacuum impregnation time in step (1) is 2-12 hours. In order to fully impregnate the impregnation, vacuum impregnation is preferably performed under stirring conditions.
[0019] The removal of chemicals by immersing in boiling water in step (1) refers to the removal of NaOH and Na2SO3.
[0020] The drying in step (1) is preferably freeze drying to prevent the wood chips from shrinking during the drying process.
[0021] The flexible wood substrate obtained in step (1) can be further cut and shaped as needed, wherein the cutting is preferably cut into a rectangular flexible wood substrate with a length of 4 cm, a width of 3 cm and a thickness of 1 mm.
[0022] In step (2), the screen is preferably a 200-mesh wooden frame screen made of nylon;
[0023] The solid wax in step (2) is at least one of beeswax and paraffin;
[0024] The heating in step (2) is heating at 60-100° C. for 0.5-3 min, preferably heating at 80° C. for 1 min;
[0025] The cooling to room temperature in step (2) refers to cooling to room temperature in less than 10 seconds.
[0026] The working electrode described in step (3) is a conductive carbon electrode; the counter electrode is a conductive carbon electrode; and the reference electrode is an Ag / AgCl electrode;
[0027] Preferably, the reference electrode in step (3) is an Ag / AgCl electrode, and a conductive carbon layer is further included between the Ag / AgCl electrode and the hydrophilic region of the wax-printed patterned flexible wood substrate to increase conductivity.
[0028] During printing in step (3), the screen frame is fixed on the printing table, the three-electrode pattern of the screen is aligned with the hydrophilic area of the wax-printed flexible wood substrate, the flexible wood substrate is fixed, the conductive carbon paste ink is poured on one end of the screen template, and the ink is evenly scraped across the screen using a scraper, and the ink is transferred to the substrate through the pores to form a pattern; after printing, the printed wood chip is placed in the air until the ink solvent is completely evaporated, and after drying, Ag / AgCl slurry is scraped on the reference electrode, and then dried to obtain a sweat ascorbic acid detection sensor based on the screen-printed electrode and the wood substrate.
[0029] In step (3), in order to improve the conductivity, the ink can be repeatedly scraped for multiple times, preferably 5 times.
[0030] In the above preparation methods, if the temperature is not clearly specified, it is assumed to be carried out at room temperature.
[0031] A sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate is prepared by the above method.
[0032] The sweat ascorbic acid detection sensor based on screen-printed electrodes and wood substrate is used for detecting ascorbic acid in sweat.
[0033] A method for detecting ascorbic acid in sweat using a sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate comprises the following steps:
[0034] (1) preparing artificial sweat with different ascorbic acid concentrations, contacting or immersing the side of the flexible wood substrate of the sensor that is not wax-dyed and printed with three electrodes with the artificial sweat, and then obtaining the oxidation current peak value of the artificial sweat with different ascorbic acid concentrations at a voltage of 0.1 V by the LSV test method of the electrochemical workstation, and obtaining a standard curve of ascorbic acid concentration and oxidation current with the ascorbic acid concentration as the abscissa and the oxidation current peak value as the ordinate;
[0035] (2) The peak value of the oxidation current of the actual sweat at a voltage of 0.1 V is tested by the LSV test method of the electrochemical workstation, and then the peak value of the oxidation current is substituted into the standard curve of step (1) to obtain the ascorbic acid concentration in the actual sweat.
[0036] The mechanism of the present invention is:
[0037] The newly developed sensor may provide a solution to the low hydrophilicity and high cost of sweat ascorbic acid sensors in the past. To address this problem, the present invention uses screen printing technology to construct a carbon electrode on a flexible wood substrate from which some lignin has been removed for detecting the ascorbic acid concentration in sweat. This sensor not only optimizes the production process and production cost, but also has excellent electrochemical properties. Moreover, thanks to the excellent water absorption of the flexible wood substrate and the use of the moisture transport system of the wood pipe, sweat can be directly and quickly transported to the electrode, demonstrating its high efficiency in practical applications. In terms of ascorbic acid detection, the sensor exhibits excellent performance indicators, including high sensitivity (0.032μA·μM -1 ), excellent selectivity, low detection limit (10μmol / L) and a wide linear response range. It can quickly and accurately monitor small changes in ascorbic acid concentrations and exhibits good repeatability and stability, providing a new strategy with practical application value for monitoring and managing health issues related to human ascorbic acid concentrations.
[0038] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0039] (1) The wood substrate of the sensor of the present invention has excellent hydrophilicity. Its water contact angle is close to 0°, and sweat samples can be transmitted through the native conduits of the wood.
[0040] (2) The sensor prepared by the present invention has good selectivity. Under the interference of various active factors, the oxidation peak of ascorbic acid can be observed at a specific oxidation potential of 0.1V.
[0041] (3) The sensor prepared by the present invention has good durability. Under the influence of different bending cycles, different bending radii, and different temperatures, the oxidation peak of ascorbic acid can be observed at a specific oxidation potential of 0.1 V. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Schematic diagram of the process of preparing hydrophilic ascorbic acid sensor with screen-printed electrodes and wood substrate from raw materials.
[0043] Figure 2 Schematic diagram of the working principle of the flexible wood sensor.
[0044] Figure 3 The microscopic morphology and delignification analysis diagram of the flexible wood substrate sensor prepared in Example 1, wherein a is the cross-sectional SEM image of the wood substrate sensor, b is the actual image of the wood substrate sensor, and c is the cross-sectional SEM image of the working electrode; d is the actual image of balsa wood before and after delignification; e is the analysis of the cellulose, hemicellulose, and lignin components of the wood before and after delignification; f is the change in the quality degradation of wood before and after delignification.
[0045] Figure 4 The changes in water absorption of the balsa wood substrate prepared in Example 1 before and after delignification. a Digital photos of liquid absorption of balsa wood at different times before and after delignification; b Liquid diffusivity of balsa wood before and after delignification; c Liquid absorption of balsa wood before and after delignification.
[0046] Figure 5 These are the performance diagrams of silk screen wax printing and silk screen carbon printing, where a is the change in the hydrophilicity of wood before and after silk screen wax printing; b is the conductive performance diagram of wood after silk screen carbon printing; and c is the EIS test diagram.
[0047] Figure 6 Sensitivity test of the sensor prepared in Example 1; it test to compare the sensitivity of the delignified balsa wood base sensor with (a) the non-delignified balsa wood base sensor and (b) the filter paper base sensor; the delignified balsa wood base sensor was subjected to CV test at different scanning rates (c) and fitting (d).
[0048] Figure 7 This is a performance test of the sensor prepared in Example 1, wherein a and b are DPV tests and fittings of ascorbic acid at different concentrations in ABS solution, and c and d are IT tests of the sensor with continuous concentration increase and enlarged diagrams.
[0049] Figure 8 The influence of different bending times (a) and bending diameters (b) on the sensitivity of the sensor prepared in Example 1.
[0050] Fig. 9 The diagram is a graph showing the change in current produced by ascorbic acid when the sensor prepared in Example 1 is subjected to the influence of different temperatures (a) and the influence of different storage time (b).
[0051] Fig.10 The simulated application of the sensor prepared in Example 1 includes (a) anti-interference test of the sensor current-time (it) characteristic, (b) DPV detection of ascorbic acid in synthetic sweat, (c) DPV simulation test of synthetic sweat on human skin; and (d) the sensor is attached to the body surface. DETAILED DESCRIPTION
[0052] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0053] Unless otherwise specified, the reagents used in the examples can be purchased from the market. Ascorbic acid, l-lactic acid, uric acid, tyrosine, acetic acid, sodium acetate, sodium chloride, potassium chloride, potassium ferrocyanide (III), sodium hydroxide, and sodium sulfite were purchased from Maclean Company. White wax was purchased from Henan Century Industrial Co., Ltd. Conductive carbon slurry and printing equipment were purchased from Dongguan Jiecheng Silk Screen Co., Ltd. Artificial sweat was purchased from Jiaying Research Company. Ag / AgCl ink was purchased from ALS Company of Japan. Wood was from Guangzhou Paper Mill.
[0054] In the embodiment, the wood chips are delignified to obtain flexible wood chips, which can be cut and shaped as needed. First, the cut wood chips are screen-printed with wax to separate the hydrophobic and hydrophilic regions. Then, carbon electrode printing is performed. After printing, the printed wood chips are placed in the air until the ink solvent is completely evaporated. After drying, Ag / AgCl ink is printed on the reference electrode to obtain a flexible wood sensor.
[0055] First, the water absorption rate of the wood-paper substrate was tested using a water absorption meter. Then, the hydrophilicity of the wood-paper substrate was determined using a contact angle tester (DCAT 21). The cross-sectional and surface scanning electron microscopy (SEM) images of the electrode and the wood substrate were taken using a field emission scanning electron microscope (HITACH). Finally, an electrochemical workstation (CHI 660e) was used for electrochemical testing.
[0056] The properties of the wood substrate in the examples were characterized by the following two methods:
[0057] Wood composition analysis: The content of cellulose, hemicellulose, and lignin in wood was determined using the NREL method, which involves grinding the wood to 40-60 mesh. Subsequently, a series of solvent extractions using water and alcohol were performed to remove non-cellulosic materials such as fat and protein from the sample. The sample was then hydrolyzed in two steps using 72% concentrated sulfuric acid and 4% dilute sulfuric acid. After the hydrolysis was completed, the solid residue (mainly lignin) was separated from the monosaccharides in the solution. The monosaccharides in the solution were quantified using high performance liquid chromatography (HPLC), while the solid residue was weighed and further chemically analyzed to determine the lignin content.
[0058] Water absorption characteristics: Use a water absorption tester to test the water absorption rate of the wood substrate. A rectangular wooden strip with a width of 3 cm, a length of 10 cm, and a thickness of 1 mm is placed on the water absorption tester for water absorption test. The amount of liquid absorbed in a specified time is recorded to measure the water absorption rate, and the liquid interface movement rate is recorded to evaluate its diffusion rate.
[0059] The performance of the sensor in the embodiment is characterized by the following method:
[0060] Electrochemical impedance spectroscopy: The test was carried out in a solution containing 5 mmol / L K3[Fe(CN)6] and 0.2 mol / L KCl.
[0061] Conductivity test: Conductive carbon paste was printed on a wood substrate and a battery and an LED light were connected to form a series path. The conductivity was judged by the brightness of the LED light.
[0062] Sensitivity characterization: IT tests of sensors on different substrates were performed in ABS solution with an ascorbic acid concentration of 25 μmol / L; CV tests of the sensors were performed at different scan rates of 0.05-0.175 V / s in a solution containing 5 mmol / L K3[Fe(CN)6] and 0.2 M KCl; DPV tests of ascorbic acid concentrations of 10-1000 μmol / L were performed in ABS solution; and one drop of 25 mmol / L ascorbic acid aqueous solution was added to a 25 μmol / L ascorbic acid aqueous solution every 30 s, and an IT test was performed.
[0063] Characterization of anti-bending performance: DPV tests were performed in 200 μmol / L ascorbic acid ABS solution after 0-500 bends (bending diameter 40 mm) and after 0-20 mm diameter bending once, and the peak current was recorded.
[0064] Characterization of resistance to temperature changes and durability: DPV tests were performed in 25 μmol / L ascorbic acid in ABS solution and the peak current was recorded.
[0065] Selective characterization: The test was carried out in ABS solution, and glucose, dopamine, lactic acid, tyrosine, and uric acid were added dropwise during the test in ABS solution containing 25 μmol / L ascorbic acid.
[0066] Sweat simulation characterization: Ascorbic acid was added to artificial sweat to a concentration of 25 μmol / L and DPV testing was performed.
[0067] ABS solution: concentration is 0.01 mol / L, pH value is 4.7, and contains 50 mmol / L NaCl.
[0068] It (current-time) test: carried out by electrochemical workstation (CHI 660e) at 0.1 V voltage, sampling interval: 0.1 s; running time: 400 s; sensitivity: 1×10 -4 A / V.
[0069] Cyclic voltammetry (CV) test: performed by electrochemical workstation (CHI 660e) in the range of -0.8 to 0.8 V; sensitivity: 1×10 -4 A / V.
[0070] Differential pulse voltammetry (DPV) test: performed by an electrochemical workstation (CHI 660e) in the range of -0.4 to 0.4 V; incremental potential: 0.004 V; pulse amplitude: 0.05 V; pulse width: 0.05 s; pulse period: 0.5 s; sensitivity: 1×10 -4 A / V.
[0071] In the embodiment, the process of preparing the substrate from the raw material and preparing the sensor by screen printing is as follows: Figure 1 As shown. After the wood chips are delignified, flexible wood chips are obtained. The flexible wood chips can be cut and formed as needed. First, the cut wood chips are screen-printed with wax to separate the hydrophobic and hydrophilic areas. Then, carbon electrode printing is performed. After printing, the printed wood chips are placed in the air until the ink solvent is completely evaporated. After drying, Ag / AgCl ink is printed on the reference electrode to obtain a flexible wood sensor.
[0072] Example 1: Preparation and application of sensor
[0073] (1) Preparation of flexible wood substrate
[0074] The wood chips, 3 cm wide, 10 cm long, and 1 mm thick, were completely immersed in 500 mL of a mixed aqueous solution containing 1 mol / L NaOH and 0.4 mol / L Na2SO3, and then quickly transferred to a vacuum chamber, where the vacuum was used to force the liquid into the wood, stirred, and soaked for 6 hours. The treated wood chips needed to be immersed in boiling deionized water several times to remove the chemicals. Then, in order to prevent the wood chips from shrinking during drying, they needed to be dehydrated by freeze drying to form the final product of the flexible wood substrate.
[0075] (2) Silk screen wax printing
[0076] The wood substrate was fixed on the screen printing table, and industrial petroleum white wax was scraped onto the wood through the screen. The wood was then placed in an oven at 80°C for 1 minute to melt the solid wax particles that passed through the mesh, turn into liquid and be absorbed by the substrate to form a hydrophobic barrier. After the baking was completed, it was taken out of the oven and allowed to cool to room temperature (<10 seconds) to form a 4 cm 2 hydrophilic reaction space.
[0077] (3) Silk screen carbon printing
[0078] Fix the screen frame on the printing table so that the three-electrode patterns of the screen are all in the central hydrophilic area of the wood. Fix the wood chip, pour the conductive carbon paste on one end of the screen template, use a scraper to evenly scrape the ink across the screen, and the ink is transferred to the substrate through the pores to form a pattern. Repeat the scraping 5 times to improve the conductivity. After printing, place the printed wood chip in the air until the ink solvent is completely evaporated. After drying, print Ag / AgCl ink on the reference electrode, and obtain a flexible wood electrode after drying.
[0079] For comparison, a sensor with a non-delignified substrate was set up, which is basically the same as Example 1, except that the wood substrate was not delignified. The other preparation processes were the same, that is, there was no step (1), and a wood chip with a width of 3 cm, a length of 10 cm, and a thickness of 1 mm was directly subjected to steps (2) and (3) to obtain a non-delignified wood substrate sensor.
[0080] For comparison, a sensor based on filter paper was set up, which is basically the same as Example 1, except that filter paper with a width of 3 cm, a length of 10 cm, and a thickness of 1 mm was directly subjected to steps (2) and (3) to obtain a paper-based sensor.
[0081] (4) Application of sensors
[0082] A sensor with a size of 4cm*2.5cm was produced.
[0083] The process diagram of preparing the screen-printed electrode and the hydrophilic ascorbic acid sensor on the wood substrate from the raw materials in this embodiment and the schematic diagram of the working principle of the sensor are shown in FIG. Figure 1 and Figure 2 As shown. The sensor uses a novel approach to combine a flexible wood substrate with screen-printed electrodes to monitor ascorbic acid in sweat. The monitoring electrodes consist of three electrodes, a working electrode (WE), a counter electrode (CE), and a reference electrode (RE). These sensors are directly applied to the skin surface to interact with sweat and analyze biochemical markers. The electrodes are designed to specifically interact with ascorbic acid, promoting its conversion to dehydroascorbic acid through an oxidation process at the electrode interface. The presence of a wax layer can control the evaporation of sweat, ensuring that only ascorbic acid reaches the electrode. In addition, the flexible wood substrate beneath the electrode has hydrophilic channels that can effectively transport sweat to the electrode surface. This design takes advantage of the natural microstructure of wood, which is modified to enhance its hydrophilicity, ensuring effective sweat absorption and transportation. The practical application of the sensor demonstrates its ability to continuously monitor ascorbic acid levels, which is critical for assessing health conditions such as sepsis. The output of the sensor can be converted into a measurable electrical signal indicating the concentration of ascorbic acid, which can be transmitted to a portable device for real-time monitoring.
[0084] Performance Test:
[0085] (1) Water absorption properties of wood substrate
[0086] Proper delignification of wood can improve its flexibility and water absorption capacity. To further elaborate on the process of lignin removal, we quantified the delignification process and presented the changes in the microstructure, physical properties, and potential of wood as a flexible electrode substrate. The properties of the wood substrate such as Figure 3 and Figure 4 As shown, Figure 3In the figure, a is a cross-sectional SEM image of the wood-based sensor. It can be seen that the surface of the flexible wood electrode still retains the original channel structure of the wood, which can use the pores of the wood to transport liquid upward by capillary action, which is beneficial to the response of the electrode; b is a physical photo, and c is a cross-sectional SEM image of the working electrode, which further shows how these channels extend through the wood piece and lead to the top to the carbon electrode. These pores form a sponge-like structure that helps absorb and transport liquids. After the substrate absorbs sweat, it is directly transported to the working electrode through these channels, making it an ideal choice for flexible electrode substrates that need to absorb and transport sweat quickly; d is a physical image before and after removing lignin from balsa wood; it illustrates the transformation from untreated wood to delignified wood. This process involves soaking the wood in an alkaline solution, which causes significant changes in color and transparency after dissolving most of the lignin and fat, indicating the effect of the chemical treatment. e is the analysis of the cellulose, hemicellulose and lignin components of the wood before and after lignin removal. It can be clearly seen that during the delignification process, the lignin content dropped from 23.8% to 19.3%, resulting in the removal of nearly 20% of the lignin, while retaining enough lignin to maintain the stability of the substrate structure. The alkaline solution also causes some cellulose and hemicellulose to hydrolyze. f is the change in the wood mass ratio before and after lignin removal; the absolute dry mass of the wood decreased by 13.1% after delignification, confirming the partial removal of lignin. Figure 4 Figure a is a digital photo of the absorption of liquid (where the liquid is water + green pigment) by fir wood over time before and after lignin removal; Figure b is a liquid diffusion diagram before and after lignin removal from fir wood. After delignification, the liquid rises to almost the same height in the same time, which indicates that delignification does not destroy the original structure of the wood and maintains its good liquid diffusion ability; Figure c is a liquid absorption diagram before and after lignin removal from fir wood, showing that the water absorption rate of the wood substrate is improved after delignification. This is due to the increase in hydrophilicity, which means that the wood can attract and retain moisture more effectively.
[0087] (2) Conductive properties of screen-printed electrodes
[0088] A battery and an LED light were connected to the flexible wood substrate prepared in step (1) of Example 1 to form a series path, and the conductivity was determined by the brightness of the LED light. Figure 5 As shown in b, it can be seen from the figure that it has good conductivity. The sensor prepared in Example 1 was tested by electrochemical impedance spectroscopy (EIS), and the results are as follows Figure 5 As shown in c, it can be seen from the figure that the resistance of the sensor is about 480 ohms, indicating good conductivity.
[0089] (3) Sensitivity characterization
[0090] To compare the electrochemical performance of the flexible wood sensor after absorbing sweat and when directly immersed in the solution, we used its performance immersed in an aqueous solution of ascorbic acid (25 μmol / L) as a benchmark (blue curve) and compared it with sensors based on delignified balsa wood, non-delignified balsa wood, and paper-based sensors. Figure 6 As shown in a and b. Figure 6 Figure a shows the current response of the delignified wood sensor and the non-delignified wood sensor after absorbing ascorbic acid solution to saturation. Compared with the non-delignified wood sensor (brown curve), the current response of the delignified wood sensor (orange curve) shows a higher initial current value and remains stable throughout the test, closely matching the blue baseline. This indicates that delignified wood as a substrate has better current transmission capabilities after absorbing the solution because the partial removal of lignin enhances the water retention of the wood, thereby improving the sensor sensitivity. Figure 6 b compares the current response of a delignified wood substrate sensor and a standard filter paper-based sensor. In this dataset, the current response of the delignified wood substrate (orange curve) is significantly better than that of the paper substrate (green curve). The paper-based sensor shows a much lower current than the baseline after absorbing the solution, which may be due to the insufficient water absorption capacity of the paper, resulting in reduced availability of reactants. In addition, the mechanical properties of paper deteriorate after absorbing water, making it prone to tearing and unsuitable for wearable sensing of human body movements. In contrast, the delignified wood substrate sensor maintains good electrical signal and mechanical integrity after absorbing water, which is critical to ensure the accuracy and reliability of electrochemical sensors. Figure 6 A set of CV graphs in c shows the current response of the sensor at different scan rates. The curves in the figure represent the current values recorded at different scan rates (0.05V / s to 0.175V / s). As can be seen from the figure, at different scan rates, the shapes of all CV curves are almost the same, and they show clear oxidation peaks. The height of the oxidation peak increases regularly with the increase in scan rate. There is a linear correlation between the peak current and the voltage and the square root of the scan rate. If a similar linear relationship is fitted, it can be obtained that the size of the oxidation peak current I is related to the scan rate (SR 1 / 2 ) and voltage U 1 / 2 linear relationship. Figure 6 The d shows the goodness of fit (R 2 ) reaches 0.9876, indicating that the sensor has very good electrochemical performance. It reflects that the sensor has good reaction kinetics and can withstand a fast scan rate, which is very important for electrochemical applications that require fast detection and fast response, allowing the sensor to effectively perform electrochemical analysis in a short time.
[0091] (4) Sensor sensitivity and stability
[0092] To explore the sensitivity and stability of the sensor, we tested it in aqueous ascorbic acid solutions with different concentrations. Figure 7 Figure a shows the current response curves of the sensor at different concentrations. It can be seen that as the concentration increases, the current also increases accordingly, showing a clear graded change, indicating that the sensor has high sensitivity to analytes of different concentrations. Figure 7 Figure b is a linear fit of the data in Figure a, showing the relationship between analyte concentration and current. The blue marks represent experimental data points, while the brown line represents the linear fitting curve. It can be observed that the data points are closely distributed around the fitting line, and the fitting degree (R 2 ) reaches 0.9573, which means that there is a strong positive correlation between the current response of the sensor and the analyte concentration, and the linear relationship is maintained in the entire measurement range. Figure 7 The c depicts the steady increase of current with increasing concentration. When the picture is enlarged ( Figure 7 As can be seen in Figure d), the current stabilizes very quickly after the concentration increases, stabilizing within 3 seconds and showing the stability and repeatability of the current signal over a long period of time. The linear increase in current indicates that the sensor performance is stable during continuous monitoring, which is an important feature for applications that monitor long-term concentration changes. In summary, Figure 7 It shows that the sensor we developed not only has high sensitivity and a good linear response range, but also maintains stable performance during continuous use.
[0093] (5) Durability of the sensor
[0094] To investigate the mechanical durability of the sensor, we folded it to different degrees and tested its performance. Figure 8 Figure a shows the current response of the sensor after different folding times, and it can be seen that even after folding up to 500 times, the current response only decreases slightly. This shows that the sensor has good mechanical durability and its performance remains relatively stable even after repeated folding. Figure 8 Figure b shows the current response of the sensor at different bending radii. The results show that even with very small bending radii, the current response remains stable with no significant changes, further confirming that the sensor can withstand large mechanical deformations without affecting its electrochemical performance. Overall, these results show that the sensor can maintain its detection capabilities even when physically altered by folding and bending, which is critical for developing stable wearable biosensors. This high level of mechanical stability ensures that the sensor can provide continuous and accurate data in practical applications such as sports activity monitoring or health status tracking.
[0095] (6) Environmental tolerance of the sensor
[0096] To investigate the environmental tolerance of the sensor, we compared its performance at different temperatures and for different exposure times. Fig. 9 The a shows the current response of the sensor to temperature changes. As can be observed, although the current increases slightly with increasing temperature (22°C, 32°C, 42°C, 52°C), the increase is not significant. This shows that normal human body temperature changes do not have a substantial impact on sensor performance, and the device can provide reliable data during daily activities even when the external temperature or body temperature fluctuates. Fig. 9 Figure b shows that the sensor maintains good performance even after 180 days of storage, with little change in electrode performance within the first 60 days of preparation. This demonstrates the excellent durability of the sensor, providing significant advantages for wearable applications and market distribution.
[0097] (7) Anti-interference performance of the sensor
[0098] In order to investigate the anti-interference property of the sensor, we performed an anti-interference test by adding various interfering substances during the ascorbic acid detection process (IT). Fig.10 The curve a shows a current curve that changes with time, which represents the current response of the sensor after adding different interfering substances to the detection system one by one when detecting the concentration of ascorbic acid. It can be seen from the figure that after adding 5mmol / L glucose, 50μmol / L tyrosine, 0.5mmol / L uric acid, 5mmol / L lactic acid and 50μmol / L dopamine, the current signal did not change significantly, indicating that the sensor was not affected by these interfering substances. The curve remains basically stable, that is, the sensor can still stably detect the concentration of ascorbic acid in the presence of interfering substances. This performance that is not affected by interfering substances is a very important feature in biosensor design, especially when testing in complex biological samples such as sweat or blood, because these samples may contain a variety of chemicals.
[0099] In order to test the performance of the sensor when worn on the human body, the sensor was subjected to simulated test experiments and tested on the human body surface. Fig.10 Figure b shows the electrochemical response of pure artificial sweat (black curve) and artificial sweat with 10 μmol / L ascorbic acid added (brown curve). It can be observed that after adding ascorbic acid, the curve has a clear peak, which indicates that the sensor can still effectively distinguish samples containing ascorbic acid from samples without ascorbic acid under strong interference conditions, thus proving that the sensor has good anti-interference ability and selectivity. Fig.10Figure c shows the current response of artificial sweat containing 10 μmol / L ascorbic acid on the surface of human skin. The current curve shows that at a certain voltage, the current has a relatively obvious peak, which indicates that the sensor can stably measure ascorbic acid at a specific voltage even during human activities. Fig.10 The sensor is designed to be flexible and can be attached to the surface of human skin and used during exercise without affecting its performance. This flexibility and wearability make the sensor ideal for continuous monitoring of human health, such as during sports or other daily activities.
[0100] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a sweat ascorbic acid detection sensor based on screen-printed electrodes and wood substrate, characterized in that The following steps are involved: Step (1): Preparation of flexible wood substrate The wood chips are immersed in a mixed aqueous solution containing NaOH and Na2SO3, and then vacuum impregnated. After the impregnation, the wood chips are immersed in boiling water to remove the chemicals, and then dried to obtain a flexible wood substrate with part of the lignin removed. Step (2): Silkscreen wax printing The flexible wood substrate is fixed on a screen printing table, and solid wax is scraped onto the flexible wood substrate through the screen, and then the flexible wood substrate is heated to melt the solid wax particles passing through the mesh, and the solid wax particles are turned into liquid and absorbed by the substrate to form a hydrophobic barrier. The hydrophilic area is not scraped with the solid wax, and the hydrophobic and hydrophilic areas are separated. The flexible wood substrate is then cooled to room temperature to obtain a wax-printed patterned flexible wood substrate; Step (3): Three-electrode printing Three electrodes, namely, a working electrode, a counter electrode and a reference electrode, are printed on the hydrophilic area of a wax-patterned flexible wood substrate, and then dried to obtain a sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate.
2. The method for preparing a sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate according to claim 1, characterized in that: The concentrations of NaOH and Na2SO3 in the mixed aqueous solution containing NaOH and Na2SO3 in step (1) are ≥1 mol / L and ≥0.4 mol / L respectively; The amount of the mixed aqueous solution containing NaOH and Na2SO3 in step (1) is sufficient to allow the wood chips to be completely immersed in the mixed aqueous solution containing NaOH and Na2SO3; The vacuum impregnation time in step (1) is 2-12 hours.
3. The method for preparing a sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate according to claim 1, characterized in that: The solid wax described in step (2) is at least one of beeswax and paraffin.
4. The method for preparing a sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate according to claim 1, characterized in that: The heating in step (2) is heating at 60-100° C. for 0.5-3 min; The cooling to room temperature in step (2) refers to cooling to room temperature in less than 10 seconds.
5. The method for preparing a sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate according to claim 1, characterized in that: The working electrode described in step (3) is a conductive carbon electrode; the counter electrode is a conductive carbon electrode; and the reference electrode is an Ag / AgCl electrode.
6. The method for preparing a sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate according to claim 5, characterized in that: A conductive carbon layer was also included between the Ag / AgCl electrode and the hydrophilic region of the wax-printed patterned flexible wood substrate.
7. The method for preparing a sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate according to claim 5, characterized in that: During printing in step (3), the screen frame is fixed on the printing table so that the three-electrode pattern of the screen is aligned with the hydrophilic area of the wax-printed flexible wood substrate, the flexible wood substrate is fixed, the conductive carbon paste ink is poured on one end of the screen template, and the ink is evenly scraped across the screen using a scraper, and the ink is transferred to the substrate through the pores to form a pattern; After printing, the printed wood chips are placed in the air until the ink solvent is completely evaporated. After drying, Ag / AgCl slurry is scraped on the reference electrode and then dried to obtain a sweat ascorbic acid detection sensor based on screen-printed electrodes and wood substrate.
8. A sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate prepared according to the method of any one of claims 1 to 7.
9. Use of the sweat ascorbic acid detection sensor based on screen-printed electrodes and wood substrate according to claim 8 in detecting ascorbic acid in sweat.
10. A method for detecting ascorbic acid in sweat using a sweat ascorbic acid detection sensor based on screen-printed electrodes and a wood substrate as claimed in claim 8, characterized in that The following steps are involved: (1) preparing artificial sweat with different ascorbic acid concentrations, contacting the side of the flexible wood substrate of the sensor that is not wax-dyed and not printed with three electrodes with the artificial sweat or immersing it in the artificial sweat, and then obtaining the oxidation current peak value of the artificial sweat with different ascorbic acid concentrations at a voltage of 0.1 V by the LSV test method of the electrochemical workstation, and obtaining a standard curve of ascorbic acid concentration and oxidation current with the ascorbic acid concentration as the abscissa and the oxidation current peak value as the ordinate; (2) The peak value of the oxidation current of the actual sweat at a voltage of 0.1 V is tested by the LSV test method of the electrochemical workstation, and then the peak value of the oxidation current is substituted into the standard curve of step (1) to obtain the concentration of ascorbic acid in the actual sweat.
Citation Information
Patent Citations
Bio-based electrochemical sensor with shaddock peel substrate and preparation method of bio-based electrochemical sensor
CN116256414A
Preparation and detection method of cobalt and carbon nanotube modified screen printing sensor electrode
CN117723611A
Printed electrodes on cork substrates and process for obtaining them
EP3708360A1
Circular pipe arc end processing device for structure installation
KR102508700B1
Electrochemical system and implantable biochemical test chip
US20230408437A1
Cited By
Green anti-pollution electrode and preparation method thereof
CN121090635A
A green anti-pollution electrode and a preparation method thereof
CN121090635B